AUDIT APLIKASI PRESENSI PADA PERUSAHAAN INDUSTRI KOSMETIK MENGGUNAKAN COBIT 5 - Honni, Honni; Lee, Francka Sakti; Isputrawan, M Fauzi; Limawal, Isabelle Ivana; Andry, Johanes Fernandes (ISTEK WIDURI, 2023)
Attendance is essential for an institution or institution; it can assess employee salaries and performance. The company that will be audited is PT Anugerah Familindo Lestari, a company that distributes beauty and hair and body care products. This company's problem is that the fingerprint machine used has an error, which causes several employees who have been absent but are not recorded in the system. Therefore, to implement a sound fingerprint attendance system, it is necessary to carry out a checking activity known as an information system audit. In conducting data and observations, the study used questionnaires and interviews with related information and document confirmation. So far, the system has been implemented to support attendance procedures. In this study, the selected domains are Deliver Service and Support (DSS) domain and Monitor, Evaluate, and Assessment (MEA) domain with a focus on IT Process DSS01, DSS04, DSS05, and MEA02. Based on the research conducted, the writer found that the average level of the DSS01 domain was 1.6, the DSS04 domain was 1.7, the DSS05 domain was 1.7, and the MEA02 domain was 1.8. In all the domains studied, the level of capability of the domain is still below the expectation; the author concludes that from the results of this capability level, PT. Anugerah Familindo Lestari still has much to do with the management and maintenance of their attendance system to increase the current level of capability because it is still quite far from the level expected by this company.